2019
DOI: 10.31000/prima.v3i2.1169
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Contextual Teaching and Learning Dan Self Regulated Learning Terhadap Kemampuan Koneksi Matematis

Abstract: Penelitian ini bertujuan untuk mengetahui pengaruh model contextual teaching and learning dan self-regulated learning terhadap kemampuan koneksi matematis siswa, ditinjau dari siswa kategori self-regulated learning (tinggi, sedang, rendah). Populasi penelitian ini adalah seluruh siswa SMK Darul Fikri Pandeglang, sampel dipilih dua kelas secara acak, yaitu kelas X RPL 1 sebagai kelas eksperimen, dan kelas X TSM 1 sebagai kelas kontrol. Pengumpulan data dilakukan melaui tes dan non tes. Tes berupa 6 soal kemampu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 1 publication
2
5
0
6
Order By: Relevance
“…The problem-solving process will provide opportunities for students to gain new knowledge by linking previously known knowledge to solve the problems they face, either in groups or alone. This is in line with what was expressed by Anwar, Pujiastuti, & Mutaqin (2019) that linking the material studied with everyday life through concepts discovered by students will provide a high concept understanding. In other words, CTL requires students to experience rather than memorize, think, and be active.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The problem-solving process will provide opportunities for students to gain new knowledge by linking previously known knowledge to solve the problems they face, either in groups or alone. This is in line with what was expressed by Anwar, Pujiastuti, & Mutaqin (2019) that linking the material studied with everyday life through concepts discovered by students will provide a high concept understanding. In other words, CTL requires students to experience rather than memorize, think, and be active.…”
Section: Discussionsupporting
confidence: 90%
“…The results obtained are supported by the research conducted by Anwar Anwar, Pujiastuti, and Mutaqin (2019); Silalahi (2018) (Anwar et al, 2019) that learning with contextual teaching and learning model affected the students' mathematical connection ability. Likewise, the results of the research conducted by Maryanti and Qadriah (2018) also concluded that there was a significant difference in the mathematical connection ability of the students using the contextual teaching and learning model with groups of students using conventional learning.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Self-regulated learning dapat dilihat dari bagaimana kemampuan siswa mengontrol dan disiplin diri dalam belajar, sehingga berdampak terhadap meningkatknya kualitas pengetahuan siswa (Gog dkk., 2020;Suhartina dkk., 2019). Tentunya siswa yang dengan tingkat self-regulated learning tinggi memiliki kecenderungan belajar lebih baik, mampu melakukan evaluasi dengan cermat, belajar secara efektif, memanfaatkan waktu lebih efisien, dan memiliki keunggulan dalam memecahkan masalah (Muhsin, Husna, 2020;Nuraisa dkk., 2019;Syahrul Anwar, Heni Pujiastuti, 2019). Oleh karena itu, self-regulated learning dapat menjadi salah satu upaya untuk mengembangkan keterampilan pemecahan masalah siswa khususnya kemampuan berpikir komputasional.…”
Section: )unclassified
“…Self-regulated learning adalah strategi yang menekankan pada kemandirian siswa dalam belajar (Gog dkk., 2020;Syahrul Anwar, Heni Pujiastuti, 2019). Self-regulated learning juga merupakan metode belajar untuk mencapai tujuan akademik dengan pengendalian diri secara mandiri sebagai bentuk tanggung jawab siswa untuk mengatur kedisiplinan dan kemampuan yang dimiliki dalam mempelajari suatu hal atas kemauannya sendiri tanpa dorongan dari siapapun (Eri Saputra, Samsul Bahri, 2019; Gog dkk., 2020; Nuraisa dkk.,…”
unclassified